Birthing outside the system : the canary in the coal mine - Dahlen, Hannah G.; Kumar-Hazard, Bashi; Schmied, Virginia (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book investigates why women choose 'birth outside the system' and makes connections between women's right to choose where they birth and violations of human rights within maternity care systems. Choosing to birth at home can force women out of mainstream maternity care, despite research supporting the safety of this option for low risk women attended by midwives. When homebirth is not supported as a birthplace option, women will defy mainstream medical advice, and if a midwife is not available choose either an unregulated careprovider or birth without assistance. This book examines the circumstances and drivers behind why women nevertheless choose homebirth by bringing legal and ethical perspectives together with the latest research on high risk homebirth (breech and twin births), freebirth, birth with unregulated careproviders and the oppression of midwives who support unorthodox choices. Stories from women who have pursued alternatives in Australia, Europe, Russia, the UK, the US, Canada, the Middle East and India are woven through the research. Insight and practical strategies are shared by doctors, midwives, lawyers, anthropologists, sociologists and psychologists on how to manage the tension between professional obligations and women's right to bodily autonomy. This book, the first of its kind, is an important contribution to considerations of place of birth and human rights in childbirth"--
OCLC-licensed vendor bibliographic record.
Keywords: Natural childbirth; Childbirth at home; Maternal health services; MEDICAL / Nursing / Maternity, Perinatal, Women's Health; SOCIAL SCIENCE / Gender Studies